2017
DOI: 10.1038/srep46746
|View full text |Cite
|
Sign up to set email alerts
|

Klf5 Mediates Odontoblastic Differentiation through Regulating Dentin-Specific Extracellular Matrix Gene Expression during Mouse Tooth Development

Abstract: Klf5, a member of the Krüppel-like transcription factor family, has essential roles during embryonic development, cell proliferation, differentiation, migration and apoptosis. This study was to define molecular mechanism of Klf5 during the odontoblastic differentiation. The expression of Klf5, odontoblast-differentiation markers, Dspp and Dmp1 was co-localized in odontoblastic cells at different stages of mouse tooth development and mouse dental papilla mesenchymal cells. Klf5 was able to promote odontoblastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 71 publications
0
26
0
Order By: Relevance
“…It has been demonstrated that the dentin is composed of mineral substance and odontoblasts formed these mineral matrix and deposited calcium [ 28 ]. All odonto/osteoblasts from dental MSCs were positively stained with ALP and Von kossa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that the dentin is composed of mineral substance and odontoblasts formed these mineral matrix and deposited calcium [ 28 ]. All odonto/osteoblasts from dental MSCs were positively stained with ALP and Von kossa.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the odonto/osteoblasts from DPSCs were most strongly stained with both. Several studies have mentioned the ALP activity as an early marker of odontoblast differentiation [ 11 , 28 ]. In our study, the expression of ALP activity was significantly higher expressed in odonto/osteoblasts when compared to undifferentiated dental MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that the levels of OCN, OPN, ALP, and Runx2 were promoted from the 7th to the 21st day (all p < 0.05; Figures 1F , G , H ). KLF5 is differentially expressed during tooth development, and may play a vital role during in the osteogenesis of hPDLCs ( Chen et al, 2009 , 2017 ; Mihara et al, 2017 ). We exhibited that KLF5 expression was enhanced notably at the 7th, 14th, and 21st day after osteogenesis induction (all p < 0.05; Figures 1I , J ).…”
Section: Resultsmentioning
confidence: 99%
“…KLF5 participates in the cell proliferation during tooth development and also relates to the mineralization of enamel and dentin matrix ( Chen et al, 2009 ). KLF5 can enhance the differentiation of odontoblasts and promote the mineral formation of dental papilla mesenchymal cells in a mouse model ( Chen et al, 2017 ). At present, the function of KLF5 in the osteogenesis of hPDLCs is still an intriguing issue waiting to be explored.…”
Section: Introductionmentioning
confidence: 99%